Pain sensitivity and analgesic use among 10,486 adults: the Tromsø study - Per-Jostein Samuelsen; Christopher Sivert Nielsen; Tom Wilsgaard; Audun Stubhaug; Kristian Svendsen; Anne Elise Eggen (BMC, 2017)
Abstract Background Increased pain sensitivity is a putative risk factor for chronic pain and consequently for analgesic use. Conversely, analgesic use may be a cause of increased pain sensitivity, e.g., through opioid-induced hyperalgesia. We aimed to study the association between pain sensitivity and analgesic use in a general population, and to test the hypothesis that increased baseline pain sensitivity is a risk factor for future persistent analgesic use. Methods The Tromsø Study (2007-08), a population-based health study, was linked with eight years of prescription data from the Norwegian Prescription Database. The cold pressor test was completed in 10,486 participants aged 30+ years, and we used cold pressor endurance time as a proxy measure of pain sensitivity. Cross-sectional associations with different measures of analgesic use were assessed. Furthermore, a cohort of 9,657 persons was followed for 4.5 years. Results In the cross-sectional analysis, increased pain sensitivity was associated with analgesic use; regular users of opioids alone were more pain sensitive than regular users of non-opioid analgesics. Increased baseline pain sensitivity was a risk factor for persistent analgesic use, i.e., using non-steroidal anti-inflammatory drugs, paracetamol, or opioids for ≥ 90 days and proportion-of-days-covered ≥ 40% (HR = 1.22, 95% CI 1.06-1.40), although not statistical significant after confounder adjustment. Conclusions Increased pain sensitivity was associated with analgesic use in general, and reduced pain tolerance was found for both opioid and non-opioid analgesic users. The data suggest that hyperalgesia is an effect of analgesics, whereas pain tolerance has little impact on future analgesic use.